The relative importance of the current account in the balance of payments in terms of the external dimensions of structural imbalance with reference to Iraq (Entrepreneurship Journal for Finance and Business, 2022)
This research seeks to address by analyzing the symmetrical imbalances between the economy and the status of the current account and what is implied by the significance of the relative importance of the current account in the balance of payments on the one hand within the framework of the internal / external overlap of developing economies in general and  Iraq , as a case study  to examine the extent of the reflection of the local economic structure on the characteristics of the current accountThere are types of imbalances in the balance of payments related to the structural characteristics of the economy i, meaning that they represent a reflection of the imbalance in its production structures, and this imbalance, namely, in the current account takes a directional turn over a long time period related to the process of economic development and its success or failure in achieving the required structural changesThe research concluded that its hypothesis is correct as far as it is concerned with Iraq and that there is a symmetry between the internal/external structural imbalance that has deteriorated in the current account, especially the trade balance, and this imbalance has taken a hidden form as a surplus in the case of the rentier economy.  It concluded that economic administration has no choice but to restructure the Iraqi economy in favor of other production sectors, as well as financing and rehabilitating infrastructure projects, in addition to striving to attract foreign investment and working to expand production capacities and reduce dependence on oil as a main source of national income.